2002
DOI: 10.1007/s00442-002-0954-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response curve analysis using nonlinear mixed models

Abstract: Nonlinear response curves are often used to model the physiological responses of plants. These models are preferable to polynomials because the coefficients fit to the curves have biological meaning. The response curves are often generated by repeated measurements on one subject, over a range of values for the environmental variable of interest. However, the typical analysis of differences in coefficients between experimental groups does not include a repeated measures approach. This may lead to inappropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(96 citation statements)
references
References 22 publications
4
90
0
2
Order By: Relevance
“…CO 2 enrichment reduced R D in the two rose cultivars. Th e parameter estimates regarding α were similar to those reported by Peek et al (2002). It was shown that the quantum effi ciency is an intrinsic characteristic, and its upper ceiling in C 3 plants is set fi rmly by physiochemical limitations (Skillman 2008).…”
Section: Discussionsupporting
confidence: 79%
“…CO 2 enrichment reduced R D in the two rose cultivars. Th e parameter estimates regarding α were similar to those reported by Peek et al (2002). It was shown that the quantum effi ciency is an intrinsic characteristic, and its upper ceiling in C 3 plants is set fi rmly by physiochemical limitations (Skillman 2008).…”
Section: Discussionsupporting
confidence: 79%
“…We specified the relationship between speed and Ṁ O 2 as a second-degree polynomial and individual fish as a random effect. Mixed models are useful as they control for temporal autocorrelation among data points in physiological response curves (Peek et al, 2002;Bolker et al, 2009;Nakagawa et al, 2013). This same model was used to test for differences between estimated (Ṁ O2E ) and observed Ṁ O2 values in the two unsteady flow treatments.…”
Section: Discussionmentioning
confidence: 99%
“…As limitações computacionais existentes até poucos anos atrás faziam com que modelos com significado biológico e análises estatísticas precisas fossem conflitantes, levando à preferência por modelos lineares e/ou polinomiais (que geram bons resultados estatísticos) em relação àqueles não-lineares, com maior significado biológico (Cacho, 1993). Entretanto, os avanços computacionais na área estatística já permitem o uso de modelos não-lineares na modelagem de fenômenos biológicos e, além disso, o correto emprego de análises de medidas repetidas no tempo (Peek et al, 2002), .…”
Section: Modelagem Como Ferramenta Para O Estudo E O Planejamento Da unclassified